Capsular nevus versus metastatic malignant melanoma – a diagnostic dilemma. (2016) - Davis, Justin; Patil, Jeevitha; Aydin, Nail; Mishra, Aparajita; Misra, Subhasis
Highlights: There are many morphologic guidelines to recognize nodal nevus cells, but there are some cases where the prediction of behavior of certain cells may not be accurate solely based on histopathological findings. Advanced histopathological techniques including implementing multiple markers should be employed in scenarios where distinguishing metastatic melanocytes from capsular nevi prove to be difficult. We strongly encourage obtaining a second opinion from a second histopathologist, preferably at a high volume center in cases where benign and malignant distinctions are difficult to make. Abstract: Introduction: A positive finding of metastatic melanoma in a sentinel lymph node is an ominous sign and a strong predictor of overall survival. In contrast, current data trends have shown that patients with benign nevus cells in the sentinel nodes do not require additional therapy since their prognosis has been shown to be similar to that of patients with negative lymph nodes. Distinguishing between benign capsular nevi and metastatic melanoma often proves to be diagnostically problematic. Case presentation: In this case report we present two cases of melanoma in which sentinel lymph node biopsies proved to be difficult in distinguishing metastatic melanocytes from capsular nevus cells. In both cases, further workup was necessary for accurate diagnoses. Discussion: A lack of standardized distinctions of benign nevus cell from melanoma pose a diagnostic pitfall. Assigning a diagnosis of malignant melanoma might seem like the safer approach to avoid a false negative, but the resultant treatment, including the possibility of additional surgical complications, may cause anxiety, discomfort, and financial instability for the patient. Current methods of distinguishing the two based solely on histology may be insufficient due to similar pathologic patterns. Conclusion: To avoid misdiagnosing a patient and performing unnecessary therapy, it would be beneficial to get a second opinion by additional histopathologists at a high volume center. Additionally, immunohistochemical staining should be carefully employed due to some overlap in commonly used markers. Using tissue morphology in conjunction with immunohistochemical staining may be the best way to make the most accurate diagnosis.